Multifunctional Benzene-Cored Covalent Organic Polymer via IEDDA Click Chemistry for Iodine Capture and pH-Responsive Drug Delivery - Cetinkaya, Ahmet; Kara, Sinem Sipahioglu; Sadak, Ali Enis; Ayhan, Mehmet Menaf; Zorlu, Yunus; Kahveci, Muhammet U. (WILEY, 2025)
Covalent organic polymers (COPs) with tunable functionality hold strong potential for pollutant capture and drug delivery. We report the synthesis of a benzene-cored COP (BeTz-COP) via a metal- and catalyst-free inverse electron-demand Diels-Alder (IEDDA) reaction between a tetra-norbornene-functionalized benzene monomer and a bifunctional tetrazine linker. This modular approach enables access to multifunctional materials under mild conditions. BeTz-COP was characterized using FTIR, SEM, EDX, TEM, and TGA, confirming its robustness. UV-Vis diffuse reflectance spectroscopy revealed a band gap of 2.01 eV for BeTz-COP, compared to 1.66 eV for the porphyrin-based PoTz-COP, as we previously reported, highlighting the impact of core structure on optoelectronic properties. Both polymers are semiconducting in optoelectronic behavior and hold promise for photocatalysis, biosensing, and light-triggered drug delivery. In cyclohexane, BeTz-COP exhibited an iodine uptake of 547 mgg-1, surpassing PoTz-COP (462 mgg-1), underscoring the aromatic core's effect on adsorption. At pH 8.50, drug loading efficiencies were 23.0% for BeTz-COP and 31.0% for PoTz-COP. Both materials showed pH-responsive doxorubicin release, with faster release under acidic conditions (pH 5.50, mimicking tumor pH) and prolonged release at physiological pH (7.40), supporting targeted drug delivery. IEDDA chemistry offers a versatile platform for designing adaptive COPs for environmental and biomedical applications.
Keywords: adsorption; covalent organic polymer; drug carrier; inverse electron demand Diels-Alder reaction; iodine uptake; FRAMEWORK; NANOPARTICLES; MICELLES; WATER; Polymer Science